Assessing Sustainable Awareness of Madrasah Ibtidaiyah Students Within the Education for Supporting Sustainable Development Goals (SDGs) Framework - Sheryl Mutiara Putri; Agung Purwanto; Irwanto Irwanto (ASEAN Journal of Educational Research and Technology, 2026)
This study aimed to analyze the level of sustainability awareness and commitment to the goals of education for sustainable development (ESD) among students in madrasah ibtidaiyah. A descriptive survey was conducted with 327 students in Sukabumi Regency using self-administered questionnaires that considered gender and grade level. Data were analyzed using descriptive statistics and one-way ANOVA. The results indicated that students demonstrated a moderate level of sustainability awareness, with an average score of 2.95. No significant differences were found across grade levels (p = 0.158), while female students showed significantly higher awareness than males (p = 0.001) in grades 3, 4, and 5. These findings suggest that gender is a more influential factor than grade level in shaping students’ sustainability awareness. The results highlight the need for gender-responsive approaches in designing effective ESD programs in primary education.